Tendências e desigualdades da mobilidade urbana no Brasil I: O uso do transporte coletivo e individual - Rafael H. M. Pereira; Lucas Warwar; Jo\~ao Pedro Figueira Amorim Parga; Jo\~ao Bazzo; Carlos Kauê Vieira Braga; Daniel Herszenhut; Marcus Saraiva (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– In this study we examine how the use of private and public transport has changed since the early 2000s in Brazilian cities. We analyzed data on the changing patterns of consumption of transportation goods and services by Brazilian families over the last 20 years. We also analyzed how urban transportation costs, the demand for public transport, and the country's vehicle fl eet have evolved in that period. All the analyses conducted pointed to a gradual and persistent trend of households moving away from public transportation towards individual modes of transport, mainly among the middle and lower classes in medium and small cities. These changing patterns caused a continuous deterioration of mobility conditions in Brazilian cities, signifi cantly increasing the time people tend to spend in traffi c. Furthermore, we demonstrate how people are unequally affected by poor mobility conditions according to their socioeconomic status, gender, and color. Finally, we show how the economic and public health crisis generated by the Covid-19 pandemic has had a profound impact on urban mobility patterns, causing a sharp decline in the numbers of daily public transport passengers across the country. Those fi ndings indicate that the Covid-19 pandemic will likely deepen the vicious cycle of passenger loss and increasing public transport fares, thus accelerating the historical trend of modal shifts from public transportation to individual modes of transport in Brazilian cities. At the end of the study we point to a few urban and transport policies that could help mitigate this trend.
Keywords: R40; R41; R48; R00; 330; urban mobility; public transport; motorization; demand; consumption behavior; inflation; commute time; Covid-19